Research on knowledge, innovation and internationalization - Larimo, Jorma; Vissak, Tiia (Emerald : EIBA, European International Business Academy, 2009)
This volume of Progress in International Business Research comprises of a selection of competitive papers from the 34th European International Business Academy Annual Conference, held in Tallinn, Estonia in December 2008, with the theme International Business and the Catching-up Economies: Challenges and Opportunities. It addresses two main issues - the internationalization process, and the role of knowledge and innovation for internationalization - both of which are important in the current economic slowdown- for catching-up and for other economies, scholars and practitioners. Divided into four parts, contributions in the first part concern the internationalization processes of multinational and international new ventures and the changes of different factors during these processes. In the second part, attention is paid to foreign operation methods such as online internationalization, the methods used in initial internationalization activities and the comparison between internationalizing with goods and services. The third part focuses on the importance of knowledge for internationalization, how it is acquired from subsidiaries or headquarters and how the state can assist. The final part of the volume discusses the role of innovation and knowledge creation in the international expansion and performance of enterprises from Central, Eastern and Southern European transition economies, but also for those entering these countries. The volume provides new theoretical, managerial and policy insights in the field of International Business research and should interest scholars, managers and policy-makers alike.
Papers from the 34th annual conference of the European International Business Academy held in Tallinn, Estonia in Dec. 2008.
Keywords: International business enterprises -- Congresses.; Globalization -- Congresses.; Knowledge management -- Congresses.; Technological innovations -- Congresses.; elektronické knihy; electronic books